An investigation of the flow characteristics in the bootdeck region of a scale model notchback saloon vehicle - Lawson, Nicholas J.; Garry, Kevin P.; Faucompret, N. (Professional Engineering Publishing, 2007)
The results of an experimental investigation of the bootdeck flow structure of a 36 per cent scale model notchback car are presented together with a general review of advanced laser diagnostic techniques suitable for large-scale wind tunnel flow measurement. The tests were used to characterize the flow behaviour over the Reynolds number range 0.74 x 10(6)-4.93 x 10(6) in the Cranfield University 2.4 m x 1.8 m wind tunnel. The experiments involved flow visualization, rear bootdeck and backlight three-dimensional stereoscopic particle image velocimetry (PIV) measurements, and mean static and unsteady static pressure measurements. Initial results from the flow visualization suggested flow asymmetries originating in the backlight region that were sensitive to the Reynolds number. The PIV data and static pressure data, however, showed little or no sensitivity of flow to Reynolds number with consistent flow structure and levels of unsteadiness from the backlight to the rear bootdeck region. At this stage no definitive reasons can be given for the discrepancies between the flow visualization and the other data, although the flow visualization data were particularly difficult to interpret near the backlight, and the near-wake structure may be bi-stable in this Reynolds number range. More detailed three-dimensional stereoscopic, time-resolved PIV flow data are now planned to quantify conclusively the correct flow structure and its sensitivities.
Keywords: particle image velocimetry automotive wakes pressure measurement flow visualization particle-image velocimetry doppler global velocimetry speckle photography piv